Red-listed Aradus laeviusculus (Hemiptera: Aradidae) inhabits burnt restoration sites in the Koli National Park, North Karelia, Finland - Viiri, Heli; Eerikäinen, Kalle (Entomologica Fennica, 2012)
We present new records of the flat bug Aradus laeviusculus Reuter, 1875, a near threatened species, in North Karelia, Eastern Finland. Three adult individuals were caught in spruce bark beetle pipe traps during the consecutive time periods of 22.V–22.VI.2006, 21.VII–22.VIII.2006 and 23.VII–25.VIII.2008 at a site that had been burnt for restoration purposes on 7.VII.2005. A. laeviusculus had been considered to be an extinct species in Finland until one specimen was found in Koli National Park in 1996. Here we discuss the possibility that slash-and-burn and restoration burn treatments may sustain the continuum of post-fire habitats essential for the A. laeviusculus population.